MEMBANGUN RUMAH IKAN DAN BIOROCK PADA PERAIRAN PULAU WARHU MALUKU TENGGARA: BUILDING FISH APARTMENT AND BIOROCK IN THE WATERS OF WARHU ISLAND SOUTHEAST MALUKU - Maimuna Renhoran; Johny Dobo; Jusron Ali Rahajaan; Syahibul Kahfi Hamid (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Fishermen in Hoat Sorbay Sub-district, Southeast Maluku Regency are dependent on the sea, this sub-district has potential waters with many fish resources because located in ten archipelagic waters which potential famous for reef fish and migration route for leatherback turtles. The high level of fishing activities followed by mores illegal activities. Generally, they uses explosives, poison, trawl nets, and cause the coral reefs damaged, then fishermen's catches will decreases. This study aims to repair the coral reefs damaged, provide training and counseling to preserving the marine environment. We use methods training, counseling and mentoring in this study and gives output 24 units of reef ball and biorock fish apartment placed in the waters of Warhu Island. Monitoring found that several types of fish such as the Acanthuridae family or surgeonfish or botana fish have occupied the biorock or fish apartment. In addition, there are fish with the Siganidae family or baronang fish and also a little bit of carnivorous fish species such as Lethrinidae family or lencam fish. In the future, the waters area of Warhu Island will become a new fishing ground, because more of the fish are the target of fishermen’s catches.